2016
DOI: 10.1242/jcs.195032
|View full text |Cite
|
Sign up to set email alerts
|

Acsl, the Drosophila ortholog of intellectual-disability-related ACSL4, inhibits synaptic growth by altered lipids

Abstract: Nervous system development and function are tightly regulated by metabolic processes, including the metabolism of lipids such as fatty acids. Mutations in long-chain acyl-CoA synthetase 4 (ACSL4) are associated with non-syndromic intellectual disabilities. We previously reported that Acsl, the Drosophila ortholog of mammalian ACSL3 and ACSL4, inhibits neuromuscular synapse growth by suppressing bone morphogenetic protein (BMP) signaling. Here, we report that Acsl regulates the composition of fatty acids and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…It has been previously shown that the enzymatic activity of Egh is reduced in egh 62d18 and egh 7 mutants ( Wandall et al, 2005 ). Here we show that both homozygous egh 62d18 and hetero-allelic egh 62d18 / egh 7 mutants also displayed fewer and larger synaptic boutons ( Figure 2,D,O and Figure 2—figure supplement 1 ; Huang et al, 2016 ). In contrast, neuronal (presynaptic) overexpression of Egh driven by the pan-neuronal nSyb-Gal4 or motor neuronal specific OK6-Gal4 led to synaptic overgrowth with more and smaller boutons ( Figure 2, D–H and O and Figure 2—figure supplement 1 ), indicating that Egh promotes bouton formation.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…It has been previously shown that the enzymatic activity of Egh is reduced in egh 62d18 and egh 7 mutants ( Wandall et al, 2005 ). Here we show that both homozygous egh 62d18 and hetero-allelic egh 62d18 / egh 7 mutants also displayed fewer and larger synaptic boutons ( Figure 2,D,O and Figure 2—figure supplement 1 ; Huang et al, 2016 ). In contrast, neuronal (presynaptic) overexpression of Egh driven by the pan-neuronal nSyb-Gal4 or motor neuronal specific OK6-Gal4 led to synaptic overgrowth with more and smaller boutons ( Figure 2, D–H and O and Figure 2—figure supplement 1 ), indicating that Egh promotes bouton formation.…”
Section: Resultsmentioning
confidence: 64%
“…We observed more boutons and satellite boutons in homozygous brn fs.107 and trans-allelic brn 1.6P6 / brn fs.107 mutants; neuronal knockdown of brn by an RNAi under the control of nSyb-Gal4 or OK6-Gal4 also resulted in NMJ overgrowth. Conversely, neuronal overexpression of Brn driven by nSyb-Gal4 or OK6-Gal4 led to fewer and larger boutons ( Figure 2, I–M and P ; Huang et al, 2016 ), recapitulating the phenotype of egh mutants. Furthermore, overexpression and knockdown of brn in muscles by C57-Gal4 or in glia by Repo-Gal4 did not affect NMJ growth ( Figure 2—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Synaptic pMad is likely part of a complex system involving receptor dynamics and endosomal processing/shuttling, that ‘tags’ axonal branches for growth, maturation, and plasticity. The molecular mechanisms known to regulate local BMP signaling in presynaptic boutons are diverse: the dynamics of nuclear importins, interactions with other trans‐synaptic and cytoplasmic signaling systems, recycling of BMP receptors through endocytic and endosomal regulation, RNA binding protein activity, phospholipid composition, and cytoskeletal regulation (Banerjee & Riordan, ; Banerjee, Venkatesan, & Bhat, ; Deshpande et al, ; Eaton & Davis, ; Fuentes‐Medel et al, ; Heo et al, ; Higashi‐Kovtun et al, ; Huang et al, ; Kim et al, ; Li et al, ; Liu et al, ; Merino et al, ; Piccioli & Littleton, ; Politano et al, ; Sulkowski et al, ; Summerville et al, ; Vanlandingham et al, ; Zhang et al, ; Zhao et al, ). Local, retrograde effects are also possible through muscle‐specific regulation of glutamate receptor composition and Gbb production/release (this study; also see Halstead et al, ; Sulkowski et al, ).…”
Section: Discussionmentioning
confidence: 99%